2004
DOI: 10.1074/jbc.m406086200
|View full text |Cite
|
Sign up to set email alerts
|

ASH1 mRNA Anchoring Requires Reorganization of the Myo4p-She3p-She2p Transport Complex

Abstract: One mechanism by which cells post-transcriptionally regulate gene expression is via intercellular and intracellular sorting of mRNA. In Saccharomyces cerevisiae, the localization of ASH1 mRNA to the distal tip of budding cells results in the asymmetric sorting of Ash1p to daughter cell nuclei. Efficient localization of ASH1 mRNA depends upon the activity of four cisacting localization elements and also upon the activity of trans-factors She2p, She3p, and Myo4p. She2p, She3p, and Myo4p have been proposed to for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 42 publications
3
18
0
Order By: Relevance
“…This corresponds to the reduction observed in HeLa cells transfected with siRNA oligonucleotides targeting myosin Va. Given the established role that myosin Va plays in the transport of mRNP complexes in a number of model systems (10,11,26), our data suggests that myosin Va is involved in the targeting of mRNA to P bodies, or the sites of P body nucleation, for storage and/or degradation.…”
Section: Myosin Va Is Necessary For Pb Assembly-examination Of the Insupporting
confidence: 74%
“…This corresponds to the reduction observed in HeLa cells transfected with siRNA oligonucleotides targeting myosin Va. Given the established role that myosin Va plays in the transport of mRNP complexes in a number of model systems (10,11,26), our data suggests that myosin Va is involved in the targeting of mRNA to P bodies, or the sites of P body nucleation, for storage and/or degradation.…”
Section: Myosin Va Is Necessary For Pb Assembly-examination Of the Insupporting
confidence: 74%
“…RNP remodeling during events such as transcription, nuclear export, and degradation have been well documented (reviewed in references 24 and 30), but little is known about remodeling during RNA localization. In Saccharomyces cerevisiae, rearrangement of the ASH1 mRNA localization complex is required for anchoring of the RNA at its destination (14). Certain RNA helicases are required for proper localization and translational regulation of oskar mRNA (33,34), hinting at a role for remodeling during RNA localization in the Drosophila oocyte.…”
mentioning
confidence: 99%
“…In any event, our results clearly show that She3p-S348E and She3p-S343E S361E are defective for ASH1 mRNA localization through a novel activity, since these mutants retain the ability to associate with Myo4p and She2p. Previously, we demonstrated that a reporter mRNA artificially tethered to She2p could not localize in a manner analogous to ASH1 mRNA, and these results implied that mRNA artificially tethered to She2p could not properly anchor at the bud tip (24). From these results we hypothesized that a molecular reorganization event occurs that releases She2p from the Myo4p-She3p-ASH1 mRNA anchoring complex.…”
Section: Vol 8 2009mentioning
confidence: 89%
“…The N terminus of She3p has the ability to associate with the type V myosin, Myo4p (7,19,47). Furthermore, She3p can simultaneously associate with Myo4p and the She2p-ASH1 mRNA complex (21,24). These observations led to the current model for ASH1 mRNA localization in which the simultaneous association of She3p with Myo4p and the She2p-ASH1 mRNA complex results in the formation of a transport particle that moves along the polarized actin cytoskeleton into the daughter cell (7,41,63).…”
mentioning
confidence: 98%